Penyadapan Pada Tindak Pidana Korupsi Perspektif Perlindungan Hak Asasi Manusia - Octaviani, Vivi; Usman, Usman; Imam Munandar, Tri (PAMPAS: Journal of Criminal Law, 2022)
The purposes of this study are 1) To find and analyze wiretapping arrangements in the criminal act of corruption from human rights’ perspective. 2) To find and analyze the urgency of wiretapping regulation on corruption in human rights’ perspective. The method used in this study is a normative-juridical research. The results of this study can be stated that wiretapping is an act carried out to obtain private information or confidential which aim of revealing the truth existence of a criminal act of corruption. Regulations regarding wiretapping in corruption crimes regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption and Law Number 30 of 2002 concerning the Commission for the Eradication of Criminal Acts of Corruption. Regarding the authority of the KPK in conducting wiretapping. However, the regulations that have regulated the wiretapping have not regulated the wiretapping in detail in its entirety, so in its implementation it often contradicts human rights. In the last three years one of the corruption laws has undergone a renewal, namely Law Number 30 of 2002 concerning the Corruption Eradication Commission as amended to become Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission. The reforms contained in the law include the renewal of rules regarding wiretapping, but unfortunately the renewal has caused controversy in the public realm. So it is necessary to establish a special law regarding wiretapping. Abstrak Tujuan dari penelitian ini adalah 1)Untuk mengetahui dan menganalisis pengaturan penyadapan pada tindak pidana korupsi perspektif perlindungan hak asasi manusia. 2)Untuk mengetahui dan menganalisis urgensi pengaturan penyadapan pada tindak pidana korupsi perspektif perlindungan hak asasi manusia. Metode yang digunakan dalam penelitian ini yaitu metode penelitian yuridis normatif. Hasil penelitian ini dapat dikemukakan bahwa penyadapan merupakan suatu perbuatan yang dilakukan untuk mendapatkan informasi yang bersifat privasi ataupun rahasia yang mempunyai tujuan untuk mengungkapkan kebenaran adanya suatu tindak pidana korupsi. Pengaturan tentang penyadapan dalam tindak pidana korupsi telah diatur didalam Undang-Undang Nomor 20 Tahun 2001 Tentang Perubahan Atas Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi dan Undang-Undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi yang didalamnya telah mengatur tentang kewenangan KPK dalam melakukan penyadapan. Akan tetapi pengaturan yang telah mengatur tentang penyadapan belum mengatur secara keseluruhan tentang penyadapan secara rinci sehingga pada pelaksanaannya sering kali bertentangan dengan hak asasi manusia. Dalam tiga tahun terakhir salah satu Undang-Undang tindak pidana korupsi telah mengalami pembaharuan yaitu Undang-Undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi sebagaimana telah diperbaharui menjadi Undang-Undang Nomor 19 Tahun 2019 Tentang Perubahan Kedua Atas Undang-Undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi. Pembaharuan yang terdapat didalam Undang-Undang tersebut termasuk pembaharuan aturan mengenai penyadapan, namun sayangnya pembaharuan itu menimbulkan kontroversi diranah publik. Sehingga perlunya dibentuk Undang-Undang secara khusus tentang penyadapan.